2004
DOI: 10.1046/j.1365-313x.2003.01961.x
|View full text |Cite
|
Sign up to set email alerts
|

Map‐based cloning of a fertility restorer gene, Rf‐1, in rice (Oryza sativa L.)

Abstract: SummaryA rice nuclear gene, Rf-1, restores the pollen fertility disturbed by the BT-type male sterile cytoplasm, and is widely used for commercial seed production of japonica hybrid varieties. Genomic fragments carrying Rf-1 were identi®ed by conducting chromosome walking and a series of complementation tests. Isolation and analysis of cDNA clones corresponding to the fragments demonstrated that Rf-1 encodes a mitochondrially targeted protein containing 16 repeats of the 35-aa pentatricopeptide repeat (PPR) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
155
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(158 citation statements)
references
References 32 publications
3
155
0
Order By: Relevance
“…I observed that the Rf-1 gene was more or less effective on both cytoplasm types: the Rf-1 derived from IR36 restored pollen fertility in a gametophytic manner in BT-type CMS (Table 1), and partially restored pollen fertility in WA-type CMS (Table 2). These results are consistent with those obtained in previous studies using indica and japonica varieties (Young and Virmani 1984, Raj and Virmani 1988, Bharaj et al 1991, 1995, Teng and Shen 1994, Yao et al 1997, Akagi et al 2004, Komori et al 2004, Wang et al 2006. At present, it is remains to be determined whether the partial restoration of pollen fertility in WA-type CMS is a pleiotropic effect of Rf1a or Rf1b (Wang et al 2006), or is due to the clustering of multiple Rf genes of the Rf-1 locus.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…I observed that the Rf-1 gene was more or less effective on both cytoplasm types: the Rf-1 derived from IR36 restored pollen fertility in a gametophytic manner in BT-type CMS (Table 1), and partially restored pollen fertility in WA-type CMS (Table 2). These results are consistent with those obtained in previous studies using indica and japonica varieties (Young and Virmani 1984, Raj and Virmani 1988, Bharaj et al 1991, 1995, Teng and Shen 1994, Yao et al 1997, Akagi et al 2004, Komori et al 2004, Wang et al 2006. At present, it is remains to be determined whether the partial restoration of pollen fertility in WA-type CMS is a pleiotropic effect of Rf1a or Rf1b (Wang et al 2006), or is due to the clustering of multiple Rf genes of the Rf-1 locus.…”
Section: Discussionsupporting
confidence: 90%
“…The single nucleotide polymorphic marker 01-45 was used to detect the Rf1b sequence according to the method of Wang et al (2006). The Rf-1A (Rf1a) gene was detected by PCR using the specific primers Rf1-3F (5′-tgatgatcgaggaggaggta-3′) and Rf1-4R (5′-aagagtattgtaggtaatgac-3′), which were designated according to the reported Rf-1A sequence (Komori et al 2004). Size of the specific PCR product was 1009 bp.…”
Section: Marker-assisted Selection (Mas)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was named differently, they all identified the same gene, ultimately called Rf1a, encoding a PPR protein of 791 amino acids and constituted of 18 PPR repeats. 6,[39][40][41] Rf1a was initially considered to be the sole gene of the Rf-1 locus restoring the BT-type CMS, but further exploration of the Rf-1 genomic region revealed a second PPR gene also functioning in fertility restoration. 6 This second restorer was named Rf1b and is likely not present in all rice restorer lines.…”
Section: Rf-ppr Genes Impede Specifically the Expression Or The Accummentioning
confidence: 99%
“…Therefore, we assume that a gene cluster (a set of two or more genes) may play the different effects on the male sterility, which was also found in the fertility restorer genes. There is a set of the Rf-1 homologous genes on chromosome 10 ( Akagi et al, 2004;Komori et al, 2004).…”
Section: Distribution Of Ptgms Genes On Rice Chromosomementioning
confidence: 99%